Tools for Responding to Patient-Initiated Verbal Sexual Harassment: A Workshop for Trainees and Faculty - Lauren E. Hock; Patrick B. Barlow; Brittni A. Scruggs; Thomas A. Oetting; Denise A. Martinez; Michael D. Abràmoff; Erin M. Shriver (Association of American Medical Colleges, 2021)
Introduction Patients are the most common source of gender-based harassment of resident physicians, yet residents receive little training on how to handle it. Few resources exist for residents wishing to address patient-initiated verbal sexual harassment themselves. Methods We developed, taught, and evaluated a 50-minute workshop to prepare residents and faculty to respond to patient-initiated verbal sexual harassment toward themselves and others. The workshop used an interactive lecture and role-play scenarios to teach a tool kit of communication strategies for responding to harassment. Participants completed retrospective pre-post surveys on their ability to meet the learning objectives and their preparedness to respond. Results Ninety-one participants (57 trainees, 34 faculty) completed surveys at one of five workshop sessions across multiple departments. Before the workshop, two-thirds (67%) had experienced patient-initiated sexual harassment, and only 28 out of 59 (48%) had ever addressed it. Seventy-five percent of participants had never received training on responding to patient-initiated sexual harassment. After the workshop, participants reported significant improvement in their preparedness to recognize and respond to all forms of patient-initiated verbal sexual harassment (p < .01), with the greatest improvements noted in responding to mild forms of verbal sexual harassment, such as comments on appearance or attractiveness or inappropriate jokes (p < .01). Discussion This workshop fills a void by preparing residents and faculty to respond to verbal sexual harassment from patients that is not directly observed. Role-play and rehearsal of an individualized response script significantly improved participants' preparedness to respond to harassment toward themselves and others.